Malawi financial markets and household food security, 1995 - International Food Policy Research Institute (International Food Policy Research Institute, 2000)
The questionnaire was administered in three rounds between February and December, 1995, to 404 households in 45 villages in five districts: Dowa, Nkhotakota, Rumphi, Mangochi, and Dedza. About half of the sample participated in credit groups by the Malawi Rural Finance Company, Malawi Mudzi Fund, MOWCACDSW's credit program 'Promotion of Micro-Enterprises for Rural Women', and Malawi Union of Savings and Credit Cooperatives; the other half of the sample either previously participated in the former credit program of the Smallholder Agricultural Credit Administration or never participated in a formal credit program. Topics include household demographics; land tenure, agricultural production, and livestock ownership; asset ownership and transactions; food and non-food consumption; credit, savings, and gift transactions; wage and self-employment income and time allocation; anthropometric status of preschoolers and their mothers. The agricultural data cover the 1993/94 and 1994/95 seasons.